2000
DOI: 10.1007/s001130050669
|View full text |Cite
|
Sign up to set email alerts
|

Kinetische Therapie zur Therapie und Prophylaxe der posttraumatischen Lungeninsuffizienz

Abstract: The effects of kinetic therapy on the oxygenation in the injured lung of 111 polytrauma patients were analysed in an open prospective study. The patient collective comprised 82 men and 29 women. For the total group, the average age was 38.3 years (+/- 16.1). The initial ISS was 39.3 points (+/- 18.9), and the APACHE II evaluated 24 h after including the patient into the study was 13.1 (+/- 5.2). The data of 3 treatment groups were evaluated: 1, acute respiratory disease (ARDS, n = 42); 2, acute lung injury (AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…CLRT improves the pulmonary gas exchange in patients with acute respiratory insufficiency (evidence level 2b) [ 25 , 222 , 223 , 237 , 238 , 265 , 267 ]. The following effects were confirmed starting at a rotational angle of ≥ 40° on each side:…”
Section: Continuous Lateral Rotation Therapymentioning
confidence: 99%
“…CLRT improves the pulmonary gas exchange in patients with acute respiratory insufficiency (evidence level 2b) [ 25 , 222 , 223 , 237 , 238 , 265 , 267 ]. The following effects were confirmed starting at a rotational angle of ≥ 40° on each side:…”
Section: Continuous Lateral Rotation Therapymentioning
confidence: 99%
“…Initially invented to prevent pressure ulcers, it rapidly became obvious that KT improves pulmonary conditions in critically ill patients. A couple of smaller studies have demonstrated beneficial effect of KT in patients with major trauma [4][5][6][7]. Recently, these results have been confirmed in a larger, prospective, randomized trial, in which KT was highly effective to prevent pulmonary complications in critically ill trauma patients [8].…”
Section: Introductionmentioning
confidence: 91%
“…2. Ventilator use has been reduced by a median [25th, 75th percentile] of 7 days (KT, 11 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], SC 18 [9-23] days). In consequence, ICU stay was reduced by a median of 8 days, and the time to discharge or referral was reduced by a median of 5 days.…”
Section: Ventilator Dependency Icu and Hospital Staymentioning
confidence: 99%